2018
DOI: 10.1021/acs.est.7b06105
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Containing, Light-Absorbing Oligomers Produced in Aerosol Particles Exposed to Methylglyoxal, Photolysis, and Cloud Cycling

Abstract: Aqueous methylglyoxal chemistry has often been implicated as an important source of oligomers in atmospheric aerosol. Here we report on chemical analysis of brown carbon aerosol particles collected from cloud cycling/photolysis chamber experiments, where gaseous methylglyoxal and methylamine interacted with glycine, ammonium, or methylammonium sulfate seed particles. Eighteen N-containing oligomers were identified in the particulate phase by liquid chromatography/diode array detection/electrospray ionization h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 76 publications
4
86
2
Order By: Relevance
“…The wintertime concentrations of nitrophenols measured in the current study are comparable to those detected in Shanghai (Li et al, 2016b), at Mt. Tai in Shandong Province of China (Desyaterik et al, 2013) and Ljubljana in Slovenia (Kitanovski et al, 2012), but the summertime concentrations observed are more comparable to those detected in the Los Angeles Basin in the US (Zhang et al, 2013). The substantially lower concentration of nitrophenols in summer may be related to rapid photodegradation in the atmosphere.…”
Section: Molecular Characterization Of Brc Aerosolssupporting
confidence: 70%
See 3 more Smart Citations
“…The wintertime concentrations of nitrophenols measured in the current study are comparable to those detected in Shanghai (Li et al, 2016b), at Mt. Tai in Shandong Province of China (Desyaterik et al, 2013) and Ljubljana in Slovenia (Kitanovski et al, 2012), but the summertime concentrations observed are more comparable to those detected in the Los Angeles Basin in the US (Zhang et al, 2013). The substantially lower concentration of nitrophenols in summer may be related to rapid photodegradation in the atmosphere.…”
Section: Molecular Characterization Of Brc Aerosolssupporting
confidence: 70%
“…Numerous studies reported that biomass burning is a dominant source of BrC in the atmosphere (Desyaterik et al, 2013;Washenfelder et al, 2015). In the current study, levoglucosan -a key tracer for biomass burning emissions (Simoneit, 2002) -was determined.…”
Section: Optical Absorption Characteristics Of Ws-brc and Wi-brcmentioning
confidence: 99%
See 2 more Smart Citations
“…The sum of sulfate and bisulfate was used to calculate c (NH 4 )2SO 4 . For cloud droplets, K H,w is used due to the low ion concentrations in cloud water (Ervens, 2015;McNeill, 2015).…”
Section: Calculating the Henry's Constantmentioning
confidence: 99%